Light lines - Teo, Esther Wan Ling (2016)
Light Lines is an interactive photo booth installation challenging the etymology of photography in the 21st century. Since Sir John Herschel and Hércules Florence coined the term “photography”, we have widely accepted its definition as “drawing with light”. This is based off the etymology of “photography” where phos means “light” and graphein means “to draw”. However, since the advent of digital photography, the digital process that operates on numbers and data has overtaken the traditional chemical process of creating a photograph with light and silver. This implies that digital photographs are simulated without the actual act of drawing with light. Through the interactive engagement of the photo booth, Light Lines hopes to challenge the user’s traditional understanding of a photograph with an alternative output from the photo booth. The output is constructed upon graphein’s other meaning, to “represent by lines drawn” by rendering the light information captured in the form of a graph and challenge that as a photograph.